Families’ experiences of the Low Arousal Approach: a qualitative study - McDonnell, Andrew Austin; Page, Andrea; Bews-Pugh, Stephanie; Morgalla, Karolina Anna; Kaur-Johal, Tarendeep; Maher, Mary (Frontiers in Psychology, 2024)
Background Parents and carers supporting a family member presenting with behaviors of concern experience heightened stress. The Low Arousal Approach is a crisis management strategy which recognizes that stress, or physiological arousal, can be expressed through behaviors of concern. This approach aims to equip parents and carers to manage behaviors in a person-centered and non-confrontational way. There is a paucity of published research exploring the experiences of families applying this approach. Methods Seventeen parents who had received training in the Low Arousal Approach were interviewed to gain their perspectives on supporting their family members using this approach. Results Thematic analysis revealed themes relating to parental stress, which was related to external pressures, isolation, family stress, and challenges in their caring role. They described encountering negative narratives relating to self-criticism and negative judgments from others. Training in the Low Arousal Approach was related to being empowered through access to evidence, increased confidence, and increased ability to advocate for their family member’s needs. Low Arousal was described as a “lifestyle” that enabled increased coping for the family unit as a whole. Discussion/conclusion Findings indicate that it is vitally important to recognize the views of parents and carers, and these are equally as important as the views of professionals. We must understand parents’ and carers’ needs in order to provide adequate support.